Effect of Gegen Qinlian Decoction on the regulation of gut microbiota and metabolites in type II diabetic rats - Xu, Jinyao; Zou, Zhenkai; Li, Xuanyi; Sun, Xiangjun; Wang, Xufeng; Qin, Feng; Abulizi, Abulikemu; Chen, Qian; Pan, Zhigang; Shen, Hexiao; Lv, Yongling; Yan, Ruicheng (Frontiers in Microbiology, 2024)
Gegen Qinlian Decoction (GGQLT) is a traditional Chinese herbal medicine that has been reported to have a significant therapeutic effect in the management of type II diabetes mellitus (T2DM). In this study, we constructed a T2DM rat model by feeding a high-fat diet and injecting streptozotocin (STZ) and tested the effects of feeding GGQLT and fecal transplantation on the physiological indices, microbiota, and metabolism of rats. The results showed that the administration of GGQLT can significantly improve the growth performance of rats and has a remarkable antihyperlipidemic effect. In addition, GGQLT altered the composition of gut microbiota by increasing beneficial bacteria such as Coprococcus, Bifidobacterium, Blautia, and Akkermansia. In addition, GGQLT elevated levels of specific bile acids by metabolomic analysis, potentially contributing to improvements in lipid metabolism. These findings suggest that GGQLT may have beneficial effects on T2DM by influencing lipid metabolism and gut microbiota. However, further studies are needed to elucidate its mechanisms and assess clinical applications.